2021
DOI: 10.1332/174426420x15834126054137
|View full text |Cite
|
Sign up to set email alerts
|

Effective strategies that enhance the social impact of social sciences and humanities research

Abstract: Background: We are witnessing increasing demand from governments and society for all sciences to have relevant social impact and to show the returns they provide to society.<br />Aims and objectives: This paper reports strategies that promote social impact by Social Sciences and Humanities (SSH) research projects.<br />Methods: An in-depth analysis of six Social Sciences and Humanities research projects that achieved social impact was carried out to identify those strategies. For each case study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 31 publications
0
65
0
1
Order By: Relevance
“…This will help to improve future HealthyAIR prototypes, technology transfer, and the adoption of new knowledge in the short term. Along the same lines, the analysis of projects that have shown to achieve social impact conducted by Aiello and colleagues [35] revealed that the participation of a range of players in the co-creation of knowledge is required to achieve such an impact. This process implies going beyond the mere dissemination of results, enabling collaboration to be established that may make it easier to co-create knowledge within the framework of the project.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This will help to improve future HealthyAIR prototypes, technology transfer, and the adoption of new knowledge in the short term. Along the same lines, the analysis of projects that have shown to achieve social impact conducted by Aiello and colleagues [35] revealed that the participation of a range of players in the co-creation of knowledge is required to achieve such an impact. This process implies going beyond the mere dissemination of results, enabling collaboration to be established that may make it easier to co-create knowledge within the framework of the project.…”
Section: Discussionmentioning
confidence: 97%
“…This is directly related to the scalability feature associated with the social impact of the research. Specifically, this would help to make advances in the replicability of HealthyAIR, by meeting one of the social impact criteria pointed out in SIOR, in which replicability of the impact as the actions based on the project findings have been successfully implemented in more than one context [35].…”
Section: Discussionmentioning
confidence: 99%
“…Yet quality relationships experienced later in life could contribute to mitigate some of those negative psychic effects and improve the emotional condition of those subjects. This result has important social impact ( 43 ): Mental health programs addressed to patients who have histories of drug addiction can be enriched with activities that support the creation and cultivation of quality relationships. Also, drug prevention campaigns tackling youth should incorporate reflection upon the quality of social relationships in night clubbing, and of violent sporadic sexual-affective relationships more particularly, and their role in substance initiation and addiction, so young people learn that close relationships of poor quality in nightlife spaces might well raise their risk to fall into drug addiction and deteriorate their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Governments and society in general are increasingly demanding that science provides a relevant social impact that is for the benefit of the entire society, without discrimination of any group. In times of crisis such as the current one, where the challenges intensify, this demand also becomes more present [24]. This article gathers evidence on challenging experiences faced by older people who were hospitalized due to COVID-19 and positive experiences that overcame age discrimination, favoring social and health care for the elderly with positive outcomes for their health, for their relatives, and for society.…”
Section: The Negative Impact Of Ageism On Healthmentioning
confidence: 99%